Transformasi Desa Mandiri: Edukasi Pencegahan Stunting Dan Terciptanya Desa Moderat Huta Toruan IX, Tarutung - Wensdy Sitindaon; Apriliana Lase; Hanna Dewi Aritonang (Jurnal Pemberdayaan Masyarakat, 2024)
Equitable development is a form of justice obtained by villages that in terms of spatial context are indeed less advantaged by the reach of infrastructure and public facilities. This obstacle is certainly not a reason to make villages independent and empower themselves. This study uses qualitative with the aim of exploring data that researchers can obtain while in the field. This research is related to the ability of North Tapanuli Regency to be able to produce independent villages. The PkM activities of the Sociology of Religion study program are a good bridge by inviting competent speakers to be able to socialize the issues of stunting and religious moderation. It is hoped that the Hutatoruan IX community will gain knowledge and be able to apply stunting and religious moderation materials. The short-term target of this PkM is to raise public awareness of stunting prevention and encourage a tolerant attitude towards differences in a multicultural society. The PKM program implemented to socialize stunting education and religious moderation has been implemented quite well. Sitnihuta Village has the opportunity to build multicultural awareness in order to strengthen religious moderation, receiving a positive response from the community, indicated by the many questions asked by the community during the PKM activity discussion session